Pengaruh Terapi Hipnotis Lima Jari untuk Menurunkan Kecemasan pada Mahasiswa Menghadapi Skripsi Prodi Keperawatan di Universitas Malahayati - Wiwin Mardiyani; Rahma Ellya; Triyoso Triyoso (Universitas Malahayati Lampung, 2024)
ABSTRACT Anxiety is a feeling of fear of something happening caused by anticipation of danger and is a signal that helps individuals to prepare to take action against threats. observation of 10 students of the Nursing Science Study Program who were compiling their thesis at Malahayati University in Bandar Lampung on March 13 2023, by conducting interviews and observations there were 7 students of the Faculty of Health Sciences who were compiling their thesis and information was obtained that all students said they felt anxiety in working on their thesis , the main difficulty is finding relevant references, fear of meeting with the supervisor, the thesis supervisor is hard to find, when working on the thesis with noisy conditions it makes the subject unable to concentrate, feels anxious, has decreased appetite, complains of frequent dizziness, anxiety, stress , lazy and hard to sleep because too much thinking about thesis. There were 3 students who did not feel anxious, were optimistic about completing their thesis on time. To determine the effect of five finger hypnotic therapy to reduce anxiety in students who are preparing their thesis at Malahayati University in 2022. Type of quantitative research. The design in this study used a pre-experimental design with a one group pretest-posttest approach. The sample in this study were Bachelor of Nursing students at the University of Malahayati. The sampling technique in this study was purposive sampling. Analysis on univariate and bivariate tests using the dependent t-test. It was found that the average value of anxiety in students who were preparing their thesis before being given five-finger hypnotic therapy was 23.1 and the average value of anxiety after being given five-finger hypnotic therapy was 11.3. From the results of the statistical test, it was obtained a p-value = 0.000 (p count α), meaning that at α = 5% it can be interpreted that there is an effect of five finger hypnosis therapy to reduce anxiety in students who are preparing their thesis at Malahayati University in 2023. There is an effect of five-finger hypnosis therapy to reduce anxiety in students who are writing their thesis at Malahayati University in 2023. It is expected that students who are writing their thesis will be active in carrying out five-finger hypnosis therapy in dealing with anxiety problems independently with the situation relax for the sake of health. Keywords: Anxiety, 5 Finger Hypnosis, Writing Thesis ABSTRAK Ansietas adalah suatu perasaan takut akan terjadinya sesuatu yang disebabkan oleh antisipasi bahaya dan merupakan sinyal yang membantu individu untuk bersiap mengambil tindakan menghadapi ancaman. observasi terhadap 10 mahasiswa Program Studi Ilmu Keperawatan yang sedang menyusun skripsi di Universitas Malahayati Bandar Lampung pada tanggal 13 Maret 2023, dengan melakukan wawancara dan observasi terdapat 7 mahasiswa Fakultas Ilmu Kesehatan yang sedang menyusun skripsi dan diperoleh informasi bahwa semua mahasiswa mengatakan merasakan kecemasan dalam mengerjakan skripsi, kesulitan yang paling utama adalah mencari referensi yang relevan, takut bertemu dengan dosen pembimbing, dosen pembimbing skripsi susah ditemui, apabila dalam mengerjakan skripsi dengan keadaan berisik membuat subyek tidak bisa berkonsentrasi, merasa gelisah, selera makan berkurang, mengeluh sering pusing, cemas, stress, malas dan sulit tidur karena terlalu memikirkan skripsi. Terdapat 3 mahasiswa tidak merasa cemas, optimis untuk menyelesaikan skripsi tepat waktu. Diketahui pengaruh terapi hipnotis lima jari untuk menurunkan kecemasan pada mahasiswa yang sedang menyusun skripsi di Universitas Malahayati Tahun 2022. Jenis penelitian kuantitatif, Rancangan dalam penelitian ini menggunakan desain pre eksperimen dengan pendekatan one group pretes-postes. Sampel dalam penelitian ini adalah mahasiswi S1 Keperawatan Universitas Malahayati sejumlah 31 orang. Teknik sampling dalam penelitian ini adalah total sampling. Analisa pada uji univariate dan bivariate menggunakan uji t-tes dependen. Didapatkan hasil bahwa nilai rata-rata kecemasan pada mahasiswa yang sedang menyusun skripsi sebelum diberi terapi hipnotis lima jari yaitu 23.1 dan nilai rata-rata kecemasan setelah diberi terapi hipnotis lima jari yaitu 11.3. Dari hasil uji statistik didapatkan nilai r = 0,000 (p hitung α), artinya pada a = 5% dapat diartikan ada pengaruh terapi hipnotis lima jari untuk menurunkan kecemasan pada mahasiswa yang sedang menyusun skripsi di Universitas Malahayati Tahun 2023. Terdapat pengaruh dari terapi hipnotis lima jari untuk menurunkan kecemasan pada mahasiswa yang sedang menyusun skripsi di Universitas Malahayati Tahun 2023. Diharapkan kepada mahasiswa yang sedang menyusun skripsi untuk aktif dalam menjalankan terapi hipnotis lima jari dalam menangani masalah kecemasan (ansietas) secara mandiri dengan keadaan rileks demi menjaga kesehatan. Kata Kunci: Kecemasan, Hipnotis 5 Jari, Menyusun Skripsi